Anomia Treatment in Patients with Herpes Simplex Encephalitis: Single-Subject Study - Marziyeh Ostadi; Leila Ghasisin (مجله پژوهش در علوم توانبخشی, 2021)
Introduction: Herpes simplex encephalitis (HSE) virus is the most severe and debilitating inflammatory disease in the central nervous system (CNS). Anomia is one of the most common language disorders in patients with HSE. No study has been done on naming treatment in patients with HSE. This study aims to compare the effect of the semantic feature analysis (SFA) and phonological components analysis (PCA), as naming treatments, in two patients with HSE virus, who had different degrees of naming problems, to find the most optimal anomia treatment.Materials and Methods: The design of the current study was ABACA reversal single-subject. Two patients with HSE underwent speech therapy at Kashani Hospital. After determining the baseline, to treat the naming problem, the first patient was first treated with PCA and then SFA, and the second patient was first treated with SFA and then PCA. The naming ability of the patients was collected in two baseline phases, two treatment phases, and finally follow-up phase. To analyze all the five-phase, within- and between-condition visual analyses were implied for (a) relative, (b) absolute, (c) median, (d) mean level change, stability envelope, and trend. Besides, the effect size involving non-overlapping data (PND) and percentage of overlapping data (POD) were calculated in trained words.Results: The within-condition analysis of patient one showed 100% of the data of each phase, while for patient two, all data except the B phase were in the stability envelope. All details about the within-condition analysis of both patients showed different trends according to the order of treatments. Between-condition analysis of patient one exhibited the total PND of all phases 100% was contrary to the patient two was less than 70%. In both patients, the improvement caused by SFA was greater than PCA. Additionally, the maintenance after SFA was more than PCA. The order of treatment presentation as providing PCA then SFA were statistically more effective.Conclusion: SFA and PCA could potentially improve the naming ability in HSE patients with anomia. Both mentioned treatments have significant effects on the increase of naming scores. As the treatment program presented SFA then PCA, respectively, we saw less maintenance in naming scores. On the other hand, providing the reverse sequence, PCA then SFA, exhibited an excellent improvement in naming scores and also more maintenance happened.